Vehicle Police Number Detection Using Yolov8 - Ramadhan, Gilang; Khairiyah, Revinda Dwi Artanti; Natania, Salwa; Harris, Abdul (MASE - Media Applied and Engineering, 2024)
This research discusses the application of the YOLOv8 object detection model in recognizing and extracting vehicle license plate numbers from vehicle images. This method leverages deep learning technology to achieve accurate and efficient detection of license plates under various visual conditions. The proposed approach utilizes deep neural networks to identify and extract license plate information with high precision. Experiments and evaluations were conducted using a diverse vehicle dataset, demonstrating YOLOv8's capability to detect license plates quickly and reliably. The experimental results show a promising accuracy level, highlighting the significant potential of this approach for vehicle license plate detection applications. The achieved accuracy rate is 90%.